Analysis of Conceptual Solutions of Universal Helical Geared Reducers - Rackov, Milan; Kuzmanović, Siniša; Knežević, Ivan; Čavić, Maja; Penčić, Marko (International Journal of Engineering and Management Sciences, 2020)
Geared reducers are mechanisms designed to reduce the number of revolutions using geared elements and nowadays they present one of the most commonly used types of mechanical transmissions in mechanical engineering. Due to the different shapes of geared elements, there are different types of geared transmissions: helical, bevel, worm, special and combined transmissions. This paper analyses only helical geared transmissions, since there is a great extent of whole this matter. Helical transmissions are analysed only with external helical gearing, since internal geared pairs represent a special and very large group of gears. Within the external helical geared transmissions, only torque transmissions are analysed, while the transmissions of motion are not analysed and they represent another large group of transmissions. Only universal gear reducers with axial, or almost-axial, parallel shafts are considered (two-stage and three-stage transmissions). Although, single-stage gear reducer produced with parallel shafts are not considered by the paper in order to reduce the area of researching. Gear reducers are most commonly delivered to customer with electric motor, known as motor geared reducer, and they are studied here extensively. Gear reducer can be also delivered without motor, only with input shaft. The basic aim of this paper is to present all characteristics and specificities of motor geared reducer in one place.